2015
DOI: 10.1074/jbc.m115.648402
|View full text |Cite
|
Sign up to set email alerts
|

The Conserved Modular Elements of the Acyl Carrier Proteins of Lipid Synthesis Are Only Partially Interchangeable

Abstract: Background: Acyl carrier protein (ACP) is required for fatty acid synthesis. Results: Exchange of domains between an ACP that is nonfunctional in Escherichia coli and E. coli ACP results in a functional protein in one direction but not the reverse. Conclusion: Incompatibility of ACP domains can reside in both helices I and II. Significance: The modular elements of ACPs are not swappable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 28 publications
4
20
0
Order By: Relevance
“…Escherichia coli ACP (called AcpP), the most thoroughly studied member of the ACP family, is an abundant, small, and negatively charged protein that is essential for growth (79). Prior work showed that expression of the ACPs from a diverse set of bacteria could replace the function of E.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Escherichia coli ACP (called AcpP), the most thoroughly studied member of the ACP family, is an abundant, small, and negatively charged protein that is essential for growth (79). Prior work showed that expression of the ACPs from a diverse set of bacteria could replace the function of E.…”
Section: Introductionmentioning
confidence: 99%
“…lactis AcpA sequences showed that specific protein sequences located largely in helix II were incompatible with an E. coli lipid synthesis enzyme(s) (9).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of an amide linkage perturbs residues in helices II and III, while presence of the ester linkage induces these perturbations as well as additional CSPs of residues in helix IV (Figure ). We note that helix II is considered the “recognition helix,” and that AcpP primarily interacts with partner proteins through helices II and III …”
Section: Figurementioning
confidence: 99%
“…It is the rate-limiting step in fatty acid biosynthesis, and is of interest in biofuel development. Despite of its importance in primary metabolism, the atomic details of its dynamics and interactions with AcpP are lacking, hindering bioengineering efforts involving FabB (Chemler et al, 2015;Gajewski et al, 2017;Zhu & Cronan, 2015).…”
Section: 2 Case Studymentioning
confidence: 99%